Bright Ideas: A Record of Invention and Misinvention - Strang, Herbert; Brock, C. E. (Charles Edmund), 1870-1938 (Salt Lake City, UT : Project Gutenberg, 2013)
"Bright Ideas: A Record of Invention and Misinvention" by Herbert Strang is a comedic novel written in the early 20th century. It follows the adventures of two young inventors, Bob Templeton and Tom Eves, as they attempt to create various inventions during a summer spent at a Dorset farm. The story revolves around their humorous escapades while navigating challenges related to their inventions and interactions with the villagers. The opening of the book introduces Templeton and Eves as they discuss their financial woes and ambitious ideas, including a smoke machine intended to aid in wartime shipping. They reflect on past failures and the struggles of being inventors with limited funds. Their conversation is humorous and filled with banter, setting a lighthearted tone. As the narrative progresses, they receive a sum of money from Templeton$1 (Bs aunt, which sparks enthusiasm for their inventions. Their discussion leads to plans for an elaborate smoke machine, foreshadowing the comedic mishaps that arise as they embark on their inventive pursuits in the countryside. (This is an automatically generated summary.)s
Release date is 2013-07-16
Produced by Al Haines
Keywords: Boys -- Juvenile fiction; Inventors -- Juvenile fiction; World War, 1914-1918 -- England -- Juvenile fiction